The Chemistry Competency Achievement of SMA Negeri 7 Palu Students Using Predict, Observe, and Explain (POE) Learning Model - Ijirana Ijirana; Sri Wahyuni (Universitas Muhammadiyah Surakarta, 2019)
This study is aimed to derive a description of learning result improvement on salt hydrolysis material by implementing POE (Predict, Observe, Explain) learning model on the students of grade XI at SMA Negeri 7 Palu. This study was a pre-experimental within Static Group Comparison design. Sampling was carried out in a simple random with class XI MIA 1 as the experiment class and XI MIA 5 as the replication class. The instruments used in this study divided into 3 competencies, the affective competency using an observation sheet, the psychomotor competency using self-assessment questionnaire and the cognitive competency using a final test. Statistical inferential analysis using t-test one right side by requiring normal and homogeneous data. The average psychmotor competency of students in the XI MIA 1 is 81, whilst for replication class is 79. The average cognitive competency of students in XI MIA 1 is 77 with deviation standard of 10.55, whilst for replication class is 75 with standard deviation of 12.98. The result of hypothesis test using t-test one right side is tcalculated> ttable or 3.32> 1.71, whilst for replication class is 1.85>1.72, so H0 was rejected. This result concludes that the implementation of POE learning model in Grade XI students at SMA Negeri 7 Palu improves learning achievement on salt hydrolysis material to be more than competency minimum standard of 70.